Peran Material Flow Cost Accounting (MFCA) dalam Pengambilan Keputusan Manajerial: A systematic Review - Keani Isnaini; Eldo Maha Putra (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the literature on the role of Material Flow Cost Accounting (MFCA) in managerial decision making. MFCA is a method used to measure and manage the flow of materials and energy in the production process and identify waste in physical and monetary units. The results show that the application of MFCA allows companies to classify costs that generate added value and costs that originate from material loss. Through the application of MFCA, management can identify material and energy points in the production process, assess operational performance and design improvement measures for company sustainability. MFCA also plays a role in providing a basis for managers as a consideration in strategic decision making, such as supporting company sustainability, production planning, and technology investment. MFCA is not only a method for measuring the production process, but also as a means of supporting managerial decisions to improve company performance and competitiveness in a sustainable manner.